Du « développement durable » à la « ville durable » : quels débats aujourd’hui ?Regards croisés à partir de la littérature francophone et anglophone - Philippe Hamman; Virginie Anquetin; Céline Monicolle (VertigO)
This paper analyzes the repertoire of the “sustainable city” by conducting a comparative review of a corpus of eighteen French and English-language journals. While the term “sustainable city” has become ubiquitous in the discourse of policy-makers, practitioners and scholars, it is unclear what it actually means. Some use this language for its practical scope and impact in the making of urban policies ; others criticize it as a tool for legitimizing or promoting growth-oriented policies (the same as “sustainable development”). This article aims at going beyond this duality. Statistical and lexical analyses using the IRaMuTeQ software are performed to examine the plural meanings given to the “sustainable city” by evidencing lexical co-occurrences. Changing and often contradictory figures are identified across a wide variety of cultural areas : the “green city”, the “city of short distances”, the “just city” and the “participatory city”. This allows us to re-embody processes, actors and issues behind the discourse and look at them as mirrors of the contemporary making of the city. Ultimately, we find the “sustainable city” to be a genuinely political repertoire – not the expression of a self-evident, overarching economic or environmental impetus.